Staphylococcus aureus Protein A Induces Human Regulatory T Cells Through Interaction With Antigen-Presenting Cells - Uebele, Julia; Habenicht, Katharina; Ticha, Olga; Bekeredjian-Ding, Isabelle (Frontiers in Immunology, 2020)
Despite continuous exposure and development of specific immunity, Staphylococcus aureus (Sa) remains one of the leading causes of severe infections worldwide. Although innate immune defense mechanisms are well understood, the role of the T cell response has not been fully elucidated. Here, we demonstrate that Sa and one of its major virulence factors protein A (SpA) induce human regulatory T cells (Tregs), key players in immune tolerance. In human PBMC and MoDC / T cell co-cultures CD4+CD25+CD127dim Tregs were induced upon stimulation with Sa and to a lower extent with SpA alone. Treg induction was strongly, but not exclusively, dependent on SpA, and independent of antigen presentation or T cell epitope recognition. Lastly, soluble factors in the supernatant of SpA-stimulated MoDC were sufficient to trigger Treg formation, while supernatants of MoDC / T cell co-cultures containing Sa-triggered Tregs displayed T cell suppressive activity. In summary, our findings identify a new immunosuppressory function of SpA, which leads to release of soluble, Treg-inducing factors and might be relevant to establish colonization.